2018
DOI: 10.1038/s41598-018-29427-1
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities for Emergency Department Sepsis Screening at Triage

Abstract: Feasibility of ED triage sepsis screening, before diagnostic testing has been performed, has not been established. In a retrospective, outcome-blinded chart review of a one-year cohort of ED adult septic shock patients (“derivation cohort”) and three additional, non-consecutive months of all adult ED visits (“validation cohort”), we evaluated the qSOFA score, the Shock Precautions on Triage (SPoT) vital-signs criterion, and a triage concern-for-infection (tCFI) criterion based on risk factors and symptoms, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…www.nature.com/scientificreports/ antimicrobials (white blood cell count). The presence of these factors could have a significant impact on clinical criteria positivity 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…www.nature.com/scientificreports/ antimicrobials (white blood cell count). The presence of these factors could have a significant impact on clinical criteria positivity 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Confounding factors influencing body temperature, heart and respiratory rates and white blood cell count included in SIRS comprehended beta-blockers, calcium-antagonists and other antiarrhythmic drugs or pace-maker DDD (heart rate), paracetamol, anti-inflammatory drugs and antimicrobials (body temperature); benzodiazepine, sedative and chronic oxygen administration (respiratory rate); immunosuppressive drugs and antimicrobials (white blood cell count). The presence of these factors could have a significant impact on clinical criteria positivity 40 .…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of 19,670 ED patients in a large academic hospital also found that qSOFA had a low positive predictive value (12%) for sepsis requiring ICU admission. 28 A prospective cohort study of 258 patients who triggered rapid response teams found that 43% met qSOFA criteria and only one-half were presumed to be infected. 29 Our findings expand on these studies and underscore the fact that hypotension, tachypnea, and altered mental status are common in conditions other than infection or sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…14,34 One retrospective analysis of undifferentiated ED patients, for example, found that qSOFA criteria were only present at a median of 0.7 h after triage in patients who were ultimately admitted to the ICU with sepsis. 28 Our study builds on and extends this literature by applying clinical criteria that closely matched the infection and SOFA criteria used by the Sepsis-3 task force to a very large and diverse cohort of patients from a large number of hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Large administrative data analyzed by the SEPSIS-3 authors suggested that a qSOFA score of ≥ 2 would rapidly identify non-ICU patients “more likely to have poor outcomes typical of sepsis,” defined as in-hospital mortality > 10%, with an area under the receiver operating characteristic (AUROC) curve of 0.81 (compared to 0.76 for the SIRS criteria; p = 0.01) 1 , 15 . The authors concluded that the new definitions should “facilitate earlier recognition and more timely management of patients with sepsis or at risk of developing sepsis 1 .” Since this assertion in 2016, numerous authors have analyzed the usefulness of qSOFA in retrospective and prospective cohorts at different points in the care continuum from pre-hospital 16 , 17 to initial triage 18 20 to the period of ED management 20 , 21 to in-patient wards and the ICU 15 ; have looked at it as a screening tool for all patients presenting to the ED 22 or for those with suspected infection 23 , 24 ; have investigated dynamic changes in qSOFA during ED stay 20 , 25 ; have analyzed its accuracy as a predictor of ICU admission, length of stay, and in-hospital mortality 26 ; have tried to improve the performance of qSOFA by add various biomarkers including lactate 27 , 28 , procalcitonin 29 , monocyte distribution width 30 , and CRP combined with mid-regional proadrenomedullin 31 or vital sign measures including heart rate variability 32 , EtCO 2 33 , and shock index 19 ; have examined its utility in high and low resource settings 27 , 29 , 34 ; and have compared it to other scoring systems including SIRS, MEWS, NEWS, and conventional SOFA 35 , 36 . All of these studies provide important clinical information and have various limitations mainly related to the data sets used, the presence or absence of serial qSOFA values, the clinical setting where the studies were performed, and the overall mortality of the cohorts.…”
Section: Introductionmentioning
confidence: 99%